2007
DOI: 10.1200/jco.2006.06.4907
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Ifosfamide With or Without Paclitaxel in Advanced Uterine Carcinosarcoma: A Gynecologic Oncology Group Study

Abstract: OS was significantly improved in arm 2, and toxicities were as expected and manageable. However, the need for active new agents persists, given that OS remains relatively poor in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
148
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(157 citation statements)
references
References 15 publications
(11 reference statements)
3
148
1
5
Order By: Relevance
“…However, responses to present-day adjuvant radiotherapy and chemotherapy are poor and clinical trials are conducted to improve prognosis by new treatment strategies. Treatment with adjuvant combined chemotherapy seems the most promising compared with single-agent chemotherapy 14,15 or radiotherapy. 16 However, more research is needed to develop the most effective treatment for patients with uterine carcinosarcomas.…”
mentioning
confidence: 99%
“…However, responses to present-day adjuvant radiotherapy and chemotherapy are poor and clinical trials are conducted to improve prognosis by new treatment strategies. Treatment with adjuvant combined chemotherapy seems the most promising compared with single-agent chemotherapy 14,15 or radiotherapy. 16 However, more research is needed to develop the most effective treatment for patients with uterine carcinosarcomas.…”
mentioning
confidence: 99%
“…The main non-hematological toxicity was grade 2 gastrointestinal reactions in 2 patients and grade 1 in the remaining 2 patients. There were no severe adverse reactions to BEV, such as bowel perforation, bleeding or blood vessel embolism, high blood pressure, or severe proteinuria (14). Thus, it may be safe to use BEV combined with chemotherapy to treat advanced persistent and/or recurrent uterine sarcomas.…”
Section: Discussionmentioning
confidence: 95%
“…Ifosfamide is the most active single agent for carcinosarcoma. Ifosfamide±cisplatin yielded favorable results in the adjuvant setting whereas ifosfamide-paclitaxel regimen clearly demonstrated a superior overall survival in the advanced setting (Homesley et al, 2007). However, this treatment is inconvenient, costly and toxicity is considerable.…”
Section: Discussionmentioning
confidence: 99%
“…GOG0108 previously showed that ifosfamide plus cisplatin offers a slight prolongation of progression-free survival but no significant overall survival benefit over ifosfamide alone in patients with advanced, persistent, or recurrent carcinosarcoma (Sutton et al, 2000). GOG0161 is the first randomized prospective trial in uterine carcinosarcoma that clearly demonstrates a superior overall survival for combination (ifosfamide and paclitaxel) chemotherapy compared to single agent treatment (ifosfamide) in the advanced setting (Homesley et al, 2007). On the other hand, data in the adjuvant treatment is more scarce.…”
Section: Introductionmentioning
confidence: 99%